The Relationship between Birth Weight, History of IMD, Exclusive Breastfeeding, and MP-ASI with Stunting in Children 0-59 Months at Pajagan Community Health Center 2023 - Mariah, Siti; Eka Sugianti, Titin (Jurnal Obstretika Scientia, 2023)
Background: Research by Mediani, et al (2023) concluded that there are seven maternal factors that contribute to the incidence of stunting in toddlers in developing countries. These factors include maternal formal education, maternal BMI, maternal height, maternal age, antenatal care, maternal mental health, and pregnancy intentions. All of these factors influence the inheritance of genes and care for stunted children, making them the main factors in the incidence of stunting in toddlers in developing countries. Research Objective: To determine the influence of birth weight, history of IMD, history of exclusive breastfeeding and history of giving MP-ASI on the incidence of stunting in children aged 0-59 months in the Pajagan Community Health Center Working Area. Research Methods: The design of this research is cross sectional. The number of samples is based on the Isaac and Michael Table with an error rate of 5%, so the total sample is 130 toddlers. The sampling technique used in this research was simple random sampling. Research Results: 36.2% suffer from stunting, 9.2% with birth weight < 2500 grams - > 4000 grams, 88.5% with a history of IMD, 95.4% with a history of exclusive breastfeeding, 99.2% with a history of giving MP- breast milk. Chi Square test results showed that there was no relationship between birth weight, history of IMD, history of exclusive breastfeeding, history of giving MP-ASI and the incidence of stunting (p value > 0.05). Conclusion and Suggestion: The research results showed that there was no relationship between the variables studied and the incidence of stunting. These variables still contribute to stunting with the risk of occurrence ranging from 1-2 times. The Pajagan Community Health Center is advised to provide health education, monitor toddler growth, maternal health and nutrition services, increase access to health services, promote cleanliness and sanitation, and establish cross-sectoral collaboration.